2018
DOI: 10.1055/s-0038-1675453
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic relevance of urokinase-type plasminogen activator (uPA) in the blood of patients with metastatic breast cancer

Abstract: In breast cancer (BC), elevated levels of urokinase-type plasminogen activator (uPA) in tumor tissue have been confirmed as a strong prognostic factor in level-of-evidence-1 studies. The aim of the present study was to evaluate the clinical relevance of uPA levels in serum of metastatic BC patients and to compare uPA with other blood-based biomarkers. 252 patients were enrolled in this prospective, multicentre study. Blood samples were collected before begin of first-line or later-line systemic treatment. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(55 reference statements)
0
7
0
1
Order By: Relevance
“…One of the main systems responsible for ECM proteolysis is the plasminogen activation system that triggers a powerful serine protease, plasmin. The central component of this system is the uPA and its receptor (uPAR), the interaction of which stimulates proteolysis of plasminogen to plasmin [135,136]. uPA is believed to play a significant role in tumor invasion and metastasis [135,136,137].…”
Section: Potential Markers Of Cancer Cell Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main systems responsible for ECM proteolysis is the plasminogen activation system that triggers a powerful serine protease, plasmin. The central component of this system is the uPA and its receptor (uPAR), the interaction of which stimulates proteolysis of plasminogen to plasmin [135,136]. uPA is believed to play a significant role in tumor invasion and metastasis [135,136,137].…”
Section: Potential Markers Of Cancer Cell Invasionmentioning
confidence: 99%
“…The central component of this system is the uPA and its receptor (uPAR), the interaction of which stimulates proteolysis of plasminogen to plasmin [135,136]. uPA is believed to play a significant role in tumor invasion and metastasis [135,136,137]. Experiments in model animals demonstrated that inhibition of uPA and/or the uPA/uPAR interaction slows down metastasis [135].…”
Section: Potential Markers Of Cancer Cell Invasionmentioning
confidence: 99%
“…29 invasion. [33][34][35] In this exploration, we found that TDZ inhibits con- Epithelial-mesenchymal transition take place during the untimely phases of the conversion of tumours into the malignant neoplasm. 44 The thought that EMT is allied with an progression of metastatic cancer cells is evidenced by the examination, which attainment of mesenchymal indicators, for example Snail, Vimentin and Twist by epithelial carcinoma cells is linked with augmented metastatic ability, [45][46][47] as is increased nuclear expression of β-catenin 9 and E-cadherin loss.…”
Section: Discussionmentioning
confidence: 88%
“…Previously, Crowley et al (1993) reported that a competitive analogue of uPA that inhibits binding of uPA with its receptor in vivo consequently inhibits metastasis in prostate cancer. Recently, serum uPA were found to be significantly elevated in breast cancer patients compared to non-malignant counterparts ( Banys-Paluchowski et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%